Assessment of Endocan with Progression and Severity of Diabetic Nephropathy in Babylon City - Ahmed M. Mosleh (Journal of Global Pharma Technology, 2019)
Background: Diabetic nephropathy (DN) is one of risk complication in type2 diabetes mellitus (T2DM) that required for new biomarker for early detection and to decrease the progression in deterioration in kidney function. Excessive angiogenesis is a main factor in the development of diabetic nephropathy. Aim: Our aim was to examine the association between serum endocan levels and urine protein creatinine ratio (PCR) as biomarker for assessment DN This study focused on evalution of endocan as biomarker for establishing diagnosis of DN and evaluate its effect on progression and developing DN Methods: In this study we evaluated endocan and levels in DN and diabetes patients without nephropathy and compared them with healthy subjects. Poor glycemic control by assess HbA1c and duration of DM are proofed to be a risk factor for DN. Endocan estimation by ELISA technique. Blood urea and creatinine and protein in urine were estimated by spectrophotometric method. Results: Endocan levels in DN was 327.9‎±106.9 and in diabetic patient without nephropathy and healthy control were (206.3‎±91.5, 122.7‎±45.7), respectively which is statistically significant at p-value<0.05. Endocan is significantly correlated with protein to creatinine ratio (PCR) and estimated glomerulofilteration rate (eGFR) at p-value<0.05. Conclusion: Endocan could be used as reliable marker for assessment diabetic nephropathyKeywords: Diabetic nephropathy, Endocan, Type2 diabetes mellitus.